The Relationship Between the Role of Posyandu Cadres and Basic Immunization Completeness in Toddlers - Ela Novitasari; Maryati Sutarno (Global Health Science Group, 2023)
Basic immunization status in children can be influenced by several factors related to community behavior. One of the strengthening factors is the support of Posyandu cadres in the implementation of Basic Immunization. However, the activeness of cadres in supporting the immunization program is still uneven. The purpose of this study is to analyze the influence and role of cadres on the completeness of basic immunization. The design of this study was Cross-sectional. The location used for this research is in Silebu village, the working area of the Pematang Serang – Banten Health Center from June to July 2023. The sample in this study is calculated based on the formula and also the target provisions. So 66 respondents (mothers of toddlers) were obtained. The sampling technique used is purposive sampling. The bivariate analysis used in this study is to determine whether there is a relationship between two variables (independent and dependent variables), namely the Chi square test. The majority of mothers who claimed their cadres were active in immunization activities had fully immunized their children according to their age, which was 39 respondents (59.1%). The results of the chi-square analysis produced an odds ratio value (OR: 5.4; 95% Confident Interval 1.67 – 28.90; p value 0.002).